2023
DOI: 10.1073/pnas.2219588120
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of pH distribution inside individual microdroplet by stimulated Raman microscopy

Abstract: Aerosol microdroplets as microreactors for many important atmospheric reactions are ubiquitous in the atmosphere. pH largely regulates the chemical processes within them; however, how pH and chemical species spatially distribute within an atmospheric microdroplet is still under intense debate. The challenge is to measure pH distribution within a tiny volume without affecting the chemical species distribution. We demonstrate a method based on stimulated Raman scattering microscopy to visualize the three-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…As documented, decreased R p not only increases the surface area-to-volume ratio favoring the gas-particle interaction (Angle et al, 2021), but may also initiate an array of reaction advantages at the air/water interface, including the enrichment of reactant and oxidant (Anglada et al, 2020), the enhancement of interior pressure (Riva et al, 2021), the distribution of electric field (Hao et al, 2022), and the amplification of light (Arroyo et al, 2022). Moreover, a stable pH gradient was observed by Wei et al (2018) in a 20 μm droplet, and this trend was recently confirmed as R p -dependent by Gong et al (2023) among the droplets within 2.9-134.6 μm. The decrease of pH toward interface may cause the distribution of different S (IV) species in aerosol, which requires further consideration in this model.…”
Section: It Relates To the Oxidations By Aqueousmentioning
confidence: 78%
“…As documented, decreased R p not only increases the surface area-to-volume ratio favoring the gas-particle interaction (Angle et al, 2021), but may also initiate an array of reaction advantages at the air/water interface, including the enrichment of reactant and oxidant (Anglada et al, 2020), the enhancement of interior pressure (Riva et al, 2021), the distribution of electric field (Hao et al, 2022), and the amplification of light (Arroyo et al, 2022). Moreover, a stable pH gradient was observed by Wei et al (2018) in a 20 μm droplet, and this trend was recently confirmed as R p -dependent by Gong et al (2023) among the droplets within 2.9-134.6 μm. The decrease of pH toward interface may cause the distribution of different S (IV) species in aerosol, which requires further consideration in this model.…”
Section: It Relates To the Oxidations By Aqueousmentioning
confidence: 78%
“…The pH increase in small samples is a general result that applies to all neat water systems with a large surface-to-volume ratio. Some experiments have recently used Raman microscopy techniques to determine the acidity of water droplets. However, they employed a pH probe and measured the acid (AH) and conjugate base (A – ) abundances.…”
Section: Results and Discussionmentioning
confidence: 99%
“…First, the relative influence of the interface is expected to be enhanced in these smaller systems, leading to a dependence of the acidity on their size. Second, in the case of microdroplets, acidity has been suggested to be nonuniform , and to change between surface and core due to their different solvation conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies indicate that microdroplets exhibit unusual acid/base catalysis, with droplets sustaining stable long-range ion and pH gradients [95][96][97][98][99] and with some evidence for superacid and basic interfaces. 100 In contrast, other studies 101 observe a homogeneous pH within the droplets, with some evidence that pH is a function of droplet size and is either lower [102][103][104] or higher 96 than or the same 101,105 as that of the corresponding bulk solution.…”
Section: Reaction Acceleration In/on Water Dropletsmentioning
confidence: 99%